PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN ASIDO KHAS BATAK JALAN BUNGA TEROMPET NO.16 KOTA MEDAN - Nainggolan, Evan Sari Maqdalena; Rahmadsyah, Agus (Relawan Jurnal Indonesia, 2024)
The aim of this research is to find out whether customer satisfaction at the Asido Khas Batak Restaurant on Jalan Terompet Bunga No. 16 Medan City is influenced by facilities and service quality. A total of 31,416 people constituted the population of this study, which used a quantitative approach. Using nonprobability sampling, a sample of 100 respondents who met the predetermined criteria was collected. Validity, reliability and classical assumption tests were used to test the data before the t test, F test and coefficient of determination were used in the research data collection method. Customer satisfaction is proven to be significantly influenced by facilities and service quality. Customer satisfaction is greatly influenced by facilities and service quality simultaneously. Service and facility quality variables can influence customer satisfaction by 63.6%, according to the adjusted coefficient of determination (Adjusted R2) of 0.636, with other variables outside the scope of this research model determining the remaining 36.4%. This indicates that the reasons behind customer happiness may still be caused by other factors.